Actions of Prolactin in the Brain: From Physiological Adaptations to Stress and Neurogenesis to Psychopathology - Torner, Luz (Frontiers in Endocrinology, 2016)
Prolactin (PRL) is one of the most versatile hormones known. It is considered an adaptive hormone due to the key roles it plays in the modulation of the stress response and during pregnancy and lactation. Within the brain, PRL acts as a neuropeptide to promote physiological responses related to reproduction, stress adaptation, neurogenesis, and neuroprotection. The action of PRL on the nervous system contributes to the wide array of changes that occur in the female brain during pregnancy and result in the attenuation of the hypothalamic–pituitary–adrenal axis. Together, all these changes promote behavioral and physiological adaptations of the new mother to enable reproductive success. Brain adaptations driven by PRL are also important for the regulation of maternal emotionality and well-being. PRL also affects the male brain during the stress response, but its effects have been less studied. PRL regulates neurogenesis both in the subventricular zone and in the hippocampus. Therefore, alterations in the PRL system due to stress or exposure to substances that reduce neurogenesis or other conditions, could contribute to maladaptive responses and pathological behavioral outcomes. Here, we review the PRL system and the role it plays in the modulation of stress response and emotion regulation. We discuss the effects of PRL on neurogenesis and neuroprotection, the putative neuronal mechanisms underlying these effects, and their contribution to the onset of psychopathological states such as depression.